Dinâmica populacional e manejo de leptocybe invasa (Hymenoptera: Eulophidae) em plantações de eucalipto - Masson, Marcus Vinicius [UNESP] (2015)
The Brazilian forest sector has assumed an important role in the society and world economy since the 1990s, producing and providing timber and non-timber products for the most diverse industry segments. The management of gall-wasp pest, Leptocybe invasa (Hymenoptera: Eulophidae), has been refined in Brazil in the nursery and field. The objectives of this study were to correlate the population dynamics of the pest with meteorological variables and evaluate chemical control efficiency in the nursery and field conditions. The L. invasa infestation indexes were evaluated in areas with average annual rainfall ranging from 800 to 1800 mm in 2 to 9 years old plants. The dynamic and fluctuation population were evaluated monthly, with the installation of 25 equidistant sticky traps in the field in 2011. The development of galls and the chemical control were evaluated in the nursery with 5 insecticides of different active ingredients. The volumetric growth of plants in the field was compared between treatments with insecticides. The Infestation Indexes in the field were higher in the average annual rainfall of 800-1100 mm. The number of adult insects and the Infestation Indexes of L. invasa in the field were higher in hotter and drier periods. The spatial distribution of the L. invasa adults tended to aggregation in the field. The gall size was similar between treatments with insecticides in the nursery. The emergence of L. invasa adults was lower with the insecticide imidacloprid at 1 g a.i./L in the nursery. The development of eucalyptus seedlings showed better volumetric development in the field, when treated in the nursery. Infestation by L. invasa was higher in warmer regions with lower average annual rainfall. This insect can be controlled in the nursery with the insecticide imidacloprid spraying at 1 g a.i./L....